Electrochemical Sensors Based on Dirac Semimental NiTe2 in the Detection of SARS-CoV-2 - Bai, Jiangyue (Langmuir : the ACS journal of surfaces and colloids, 2025)
In the present study, a topological semimetal NiTe2-based electrochemical biosensor was designed and fabricated, leveraging the material's inherent topological surface state and conductive bulk properties. The NiTe2 electrode was fabricated via mechanical exfoliation from a high-quality NiTe2 single crystal. Owing to its robust layered structure and unique Dirac surface states, the topological semimetal NiTe2 facilitates rapid electron transfer at the electrode surface, thereby enhancing the sensor's performance. The developed biosensor showed a linear response range for DNA concentrations spanning from 10-15 to 10-7 M, with a detection limit as low as 10-16 M. In contrast, its detection response toward RNA was more sensitive, covering a concentration range of 10-18 to 10-15 M. Furthermore, this sensor was employed for the detection of synthetic SARS-CoV-2 pseudovirus at a concentration of 1000 copies/mL. The results demonstrated that the sensor could effectively differentiate between negative and positive samples, exhibiting excellent sensitivity, specificity, and stability. Consequently, the NiTe2-based biosensor possesses significant potential for application in the clinical diagnosis of SARS-CoV-2 pathogens and other acute infectious diseases